Correction of Immunity Disorders, Therapy of Intestinal Infections and Disbiosis in Children (Clinical Review) - M. G. Romantsov; O. V. Tikhomirova (Антибиотики и Химиотерапия)
Acute viral and bacterial intestinal infections in children provoke the Th2 immune response, resulting in development of severe and complicated forms of the disease and sustained by the disbiotic disturbances due to unnecessarily prolonged use of antibacterial drugs. Cycloferon, an early inductor of interferon-1 and -2, was shown to be safe and efficient in the complex therapy of the intestinal infections. It promoted generation of the Th2 immune response and decrease of the repeated isolation of the pathogen with normalization of the disease clinical signs. The host intestinal microflora was normalized and the level of the opportunistic organisms decreased.